2014
DOI: 10.3171/2013.12.jns132090
|View full text |Cite|
|
Sign up to set email alerts
|

Hockey Concussion Education Project, Part 2. Microstructural white matter alterations in acutely concussed ice hockey players: a longitudinal free-water MRI study

Abstract: Object Concussion is a common injury in ice hockey and a health problem for the general population. Traumatic axonal injury has been associated with concussions (also referred to as mild traumatic brain injuries), yet the pathological course that leads from injury to recovery or to long-term sequelae is still not known. This study investigated the longitudinal course of concussion by comparing diffusion MRI (dMRI) scans of the brains of ice hockey players before and after a concussion. Methods The 2011–2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 39 publications
3
84
1
Order By: Relevance
“…53 Collegiate ice hockey players exhibited similar white matter changes over the course of a season. [54][55][56][57] In addition, repetitive subconcussive head impacts in collegiate American football players have been linked, in a dose-dependent manner, to deficits in BBB integrity, potential loss of white matter integrity, and cognitive dysfunction. 58 These findings probably reflect some level of risk for youths who sustain repetitive subconcussive head impacts, although little research has been devoted specifi cally to this topic.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…53 Collegiate ice hockey players exhibited similar white matter changes over the course of a season. [54][55][56][57] In addition, repetitive subconcussive head impacts in collegiate American football players have been linked, in a dose-dependent manner, to deficits in BBB integrity, potential loss of white matter integrity, and cognitive dysfunction. 58 These findings probably reflect some level of risk for youths who sustain repetitive subconcussive head impacts, although little research has been devoted specifi cally to this topic.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…Clinical neuroimaging studies, including conventional MRI, are normal in the majority of cases. 17 For this reason, authors of recent studies have aimed to apply even more sophisticated neuroimaging techniques to this condition, including magnetoencephalography, 53 diffusion tensor imaging (DTI), 11,25,29,31,44,47 and task-based functional MRI (fMRI). 7,26,35,49 Despite detecting changes between groups of concussion patients and healthy controls, none of these techniques has emerged as a useful clinical tool that contributes to the management of acute SRC or PCS.…”
mentioning
confidence: 99%
“…A more recent DTI and concussion systematic review [49] suggested that the most consistent findings were decreased mean diffusivity and/or an increase in fractional anisotropy in white matter within 6 months post-concussion [66][67][68][69][70], but these findings are not universal (i.e., the opposite patterns have also been reported in other studies) [56,62,71]. In addition, reduced radial diffusivity has been reported [68,[72][73][74], but increase and decrease in axial diffusivity have been described [68,69].…”
Section: Neuroimagingmentioning
confidence: 83%